Variability in the Aerobic Fitness-Related Dependence on Respiratory Processes During Muscle Work Is Associated With the ACE-I/D Genotype - Gasser, Benedikt; Frei, Annika; Niederseer, David; Catuogno, Silvio; Frey, Walter O.; Flück, Martin (Frontiers in Sports and Active Living, 2022)
Background The efficiency of aerobic energy provision to working skeletal muscle is affected by aerobic fitness and a prominent insertion/deletion polymorphism in the angiotensin-converting enzyme (ACE-I/D) gene for the major modulator of tissue perfusion. We assessed whether variability in the fitness state is dependent on the contribution of multiple aspects of oxygen transport to the development of muscle power, and the respective control coefficients, are associated with the ACE-I/D genotype. Methods Twenty-five women and 19 men completed a ramp test of cycling exercise to exhaustion during which serial steps of oxygen transport [oxygen uptake (L O2 min−1) (VO2), minute ventilation in (L min−1) (VE), cardiac output in equivalents of L min−1 (Q), arterial oxygen saturation (SpO2), muscle oxygen saturation (SmO2), and total hemoglobin concentration (g dL−1) (THb) in Musculus vastus lateralis and Musculus gastrocnemius, respiration exchange ratio (RER)], blood lactate and glucose concentration, were continuously monitored. The contribution/reliance of power output (PO) on the parameters of oxygen transport was estimated based on the slopes in Pearson's moment correlations (|r| > 0.65, p < 0.05) vs. power values over the work phase of the ramp test, and for respective fractional changes per time (defining control coefficients) over the rest, work, and recovery phase of the ramp test. Associations of variability in slopes and control coefficients with the genotype and aerobic fitness were evaluated with ANOVA. Results All parameters characterizing aspects of the pathway of oxygen, except THb, presented strong linear relationships [(|r| > 0.70) to PO]. Metabolic efficiency was 30% higher in the aerobically fit subjects [peak oxygen uptake (mL O2 min−1) (VO2peak) ≥ 50 ml min−1 kg−1], and energy expenditure at rest was associated with the fitness state × ACE-I/D genotype, being highest in the fit non-carriers of the ACE D-allele. For VO2, VE, and RER the power-related slopes of linear relationships during work demonstrated an association with aerobic fitness, being 30–40% steeper in the aerobically fit than unfit subjects. For VE the power-related slope also demonstrated an association with the ACE-I/D genotype. For increasing deficit in muscle oxygen saturation (DSmO2) in Musculus vastus lateralis (DSmO2 Vas), the power-related slope was associated with the interaction between aerobic fitness × ACE-I/D genotype. Conclusion Local and systemic aspects of aerobic energy provision stand under influence of the fitness state and ACE-I/D genotype. This especially concerns the association with the index of the muscle's mitochondrial respiration (SmO2) which compares to the genetic influences of endurance training.